2x+x+4+x+x+x-x-3=92

Simple and best practice solution for 2x+x+4+x+x+x-x-3=92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+x+4+x+x+x-x-3=92 equation:


Simplifying
2x + x + 4 + x + x + x + -1x + -3 = 92

Reorder the terms:
4 + -3 + 2x + x + x + x + x + -1x = 92

Combine like terms: 4 + -3 = 1
1 + 2x + x + x + x + x + -1x = 92

Combine like terms: 2x + x = 3x
1 + 3x + x + x + x + -1x = 92

Combine like terms: 3x + x = 4x
1 + 4x + x + x + -1x = 92

Combine like terms: 4x + x = 5x
1 + 5x + x + -1x = 92

Combine like terms: 5x + x = 6x
1 + 6x + -1x = 92

Combine like terms: 6x + -1x = 5x
1 + 5x = 92

Solving
1 + 5x = 92

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 5x = 92 + -1

Combine like terms: 1 + -1 = 0
0 + 5x = 92 + -1
5x = 92 + -1

Combine like terms: 92 + -1 = 91
5x = 91

Divide each side by '5'.
x = 18.2

Simplifying
x = 18.2

See similar equations:

| 2(r+1)=9 | | -6.3(x+3.7)+7.65x=-1.1x-38.99 | | 2x/5=-8 | | 7x-14y=7 | | 7x+-14y=7 | | f-8-3f=37f+4 | | 3y-3=5y-5 | | f-8-3f=3-7f | | 84-3=6y+17 | | 11x=7x-20 | | 23-x=22 | | (2x+1/3)^2=0 | | 55=(3x-1)(5) | | 2(2k-5)-k=4-(3k+7) | | 49-x=14 | | -16-8= | | 26X+12=5(5X+7) | | 10+2-x/3=7 | | 32n+12-20=12n+16+1 | | 9d/12-d/12 | | v*7=8 | | 70=(x+4)(7) | | m*4=-13 | | (-8x-4y/2x)+(6x-11y/2x) | | 6x+10=-6+58 | | 2(y+5)=3(y-15)+20 | | 4=(.300+x)(.200+x) | | 1/4(x-12) | | 15x+10y=90 | | -1/2(8+6) | | 15x+10x=90 | | 7(8-3)= |

Equations solver categories